A Igualdade e suas naturezas normativas: da axiologia à dogmática jurídica / The Equality and its normative natures: from axiology to legal dogmatic - Di Lorenzo, Wambert Gomes (REVISTA QUAESTIO IURIS, 2016)
Trabalho enviado em 08 de setembro de 2015. Aceito em 25 de outubro de 2015. DOI: 10.12957/rqi.2016.18495 Resumo O conceito jurídico da igualdade desde a axiologia à dogmática jurídica. Na perspectiva clássica igualdade é um tipo de relação que propõe critérios de superação da desigualdade natural de todos os seres e que tem consequências jurídicas imediatas. Na perspectiva da axiologia jurídica, além de um valor meta-jurídico, a igualdade é um valor jurídico-constitucional que maximiza a concreção nas normas jurídicas. Do ponto de vista da dogmática jurídica, apesar do senso comum ter consagrado a igualdade como um princípio, jurídico, ela apresenta uma multiplicidade de naturezas jurídicas, sendo também, além de valor constitucional e princípio jurídico, regra e postulado normativo. Palavras-chave: Igualdade, Teoria da Norma, Teoria dos Princípios, Axiologia Juridica, Constitucionalismo de Valores Abstract The legal actualization of equality according to its various normative nature. Normative monism hinders the effectiveness of equality by considering it exclusively as a legal principle disregarding its otherwise normative nature. This paper aims to demonstrate that equality is not just a legal principle and to describe its various normative nature. The approach method is qualitative research from bibliographic sources based on which it analyses the actualization of equality from the perspective of Humberto Avila's Theory of Principles’ distinction between principle, rule and normative postulate. As an outcome, it proposes that from the legal axiology perspective, moreover than being a metalegal value, equality is a normative constitutional value that maximizes the actualization of legal norms. From the legal dogmatic perspective, it concludes that equality is also a legal principle, a rule and a normative postulate. Keywords: Equality. Theory of legal norms. Theory of Legal Principles. Legal axiology. Constitutionalism of values